The relationship between the frequency of number-puzzle use and baseline cognitive function in a large online sample of adults aged 50 and over - Brooker,H; Wesnes,KA; Ballard,C; Hampshire,A; Aarsland,D; Khan,Z; Stenton,R; Megalogeni,M; Corbett,A (International Journal of Geriatric Psychiatry, 2019)
© 2019 John Wiley & Sons, Ltd. Objective: Establishing affordable lifestyle interventions that might preserve cognitive function in the aging population and subsequent generations is a growing area of research focus. Data from the PROTECT study has been utilised to examine whether number-puzzle use is related to cognitive function in older adults. Methods: Data from 19 078 healthy volunteers aged 50 to 93 years old enrolled on the online PROTECT study were evaluated for self-reported frequency of performing number puzzles. Two cognitive-test batteries were employed to assess core aspects of cognitive function including reasoning, focussed and sustained attention, information processing, executive function, working memory, and episodic memory. Analysis of covariance was used to establish the differences between the six frequency groups. Results: Highly statistically significant main effects of the frequency of performing number puzzles were seen on all 14 cognitive measures, with P values of less than 0.0004. Interestingly, participants who reported engaging in number puzzles more than once a day had superior cognitive performance on 10 core measures compared with all other frequency groups, although not all were statistically significant. Conclusions: This study has identified a close relationship between frequency of number-puzzle use and the quality of cognitive function in adults aged 50 to 93 years old. In order to determine the value of these findings as a potential intervention, further research should explore the type and difficulty of the number puzzles. These findings further contribute to the growing evidence that engaging in mentally stimulating activities could benefit the brain function of the ageing population.